Our experience with the use of unilateral biportal endoscopic lumbar interbody fusion (UBLIF) and posterior lumbar interbody fusion (PLIF) in the treatment of patients with spinal stenosis of the lumbar spine - Ia. V. Fishchenko; I. V. Roy; A. A. Vladymirov; L. D. Kravchuk; R. I. Blonskyi (Patologìâ)
In addition to endoscopic discectomy, patients with stenosis of the spinal canal of the lumbar spine quite often undergo endoscopic decompression and / or stabilization. Spinal endoscopic surgery has several advantages compared to open operations, however, the lack of differences in long-term clinical results, a small workspace with a limited field of view and a large learning curve compared to conventional operations are disadvantages of endoscopic spinal surgery.